Topical and systemic retinoids for the treatment of cutaneous viral warts: A systematic review and meta‐analysis. Issue 1 (15th December 2020) - Oren‐Shabtai, Meital; Snast, Igor; Noyman, Yehonatan; Lapidoth, Moshe; Sherman, Shany; Mimouni, Daniel; Hodak, Emmilia; Levi, Assi
Abstract: Cutaneous viral warts (CVW), caused by human papillomavirus, often have a self‐limited course. However, some patients experience a recalcitrant disease despite treatment. Retinoids are considered the mainstay of therapy in many dermatologic diseases. Data on their use for viral warts are limited. To systematically review the published evidence on the efficacy and safety of retinoids for the treatment of CVW. A systematic review and meta‐analysis of topical or systemic retinoid treatment for CVW was performed in accordance with the PRISMA statement. The primary outcome was clinical response; secondary outcomes were recurrence rate and adverse events. Fourteen publications including 399 patients treated exclusively with retinoids (65% topical, 35% systemic) were evaluated. The complete response rate was 64% (95% CI, 46‐78%; I 2 =80%) for topical treatment and 61% (95% CI, 44‐76%; I 2 =69%) for systemic treatment. The most common side effects were irritant contact dermatitis and cheilitis, respectively. Relapse rates were 6% and 17%, respectively. The reviewed studies were considerably heterogenous and most lacked a control group. Both topical and systemic retinoids are effective and safe as monotherapy for CVW. Further studies are required to determine their exact role in this setting.